2022
DOI: 10.1371/journal.pbio.3001684
|View full text |Cite
|
Sign up to set email alerts
|

ROS and cGMP signaling modulate persistent escape from hypoxia in Caenorhabditis elegans

Abstract: The ability to detect and respond to acute oxygen (O2) shortages is indispensable to aerobic life. The molecular mechanisms and circuits underlying this capacity are poorly understood. Here, we characterize the behavioral responses of feeding Caenorhabditis elegans to approximately 1% O2. Acute hypoxia triggers a bout of turning maneuvers followed by a persistent switch to rapid forward movement as animals seek to avoid and escape hypoxia. While the behavioral responses to 1% O2 closely resemble those evoked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…C. elegans dramatically increases its locomotory speed when O 2 levels decrease rapidly from preferred (7%) to aversive hypoxia (1%) 22 . Double mutant animals for the G proteins gpa-3 and odr-3 are defective in locomotory response to acute drop of O 2 tension 22 , implicating GPCR-regulation of this response. To test this notion, we assessed all GPCR mutants for their responses to acute hypoxia (Supplementary Data 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…C. elegans dramatically increases its locomotory speed when O 2 levels decrease rapidly from preferred (7%) to aversive hypoxia (1%) 22 . Double mutant animals for the G proteins gpa-3 and odr-3 are defective in locomotory response to acute drop of O 2 tension 22 , implicating GPCR-regulation of this response. To test this notion, we assessed all GPCR mutants for their responses to acute hypoxia (Supplementary Data 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further complicating the directionality between GUCY2C, mitochondrial integrity, ROS production, and ROS scavenging is the apparent feedback loop between oxidative stress and cGMP signaling that is suggested from our data and may be conserved across species. Recent work exploring the relationship of ROS and cGMP in C. elegans revealed that mutated mitochondrial ETC complexes I or III or exposure to paraquat, a lipid membrane oxidation agent, increases cGMP accumulation and is prevented by pretreatment with antioxidants 74 . This finding parallels our mouse data; MPTP upregulates Gucy2c mRNA in the SNpc, but not in the VTA, which is comparitively resilient to mitochondrial toxins and has lower levels of oxidative stress at baseline 38 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that mitochondrial ROS alters C. elegans behavior [ 32 , 57 , [78] , [79] , [80] ]. Collectively, these reports have motivated questions regarding selectivity in ROS signaling cascades – in terms of origin and biological targets.…”
Section: Discussionmentioning
confidence: 99%